The abnormal Qur’anic readings are read in light of the theory of linguistic preference (Journal of the College of Basic Education, 2025)
The explanatory and linguistic texts recorded some Qur’anic readings and marked an abnormal area; Sorry, you have exceeded the set admission criteria Although some Arabs use it; However, this use did not reach the level of popularity and frequency. This anomaly was not arbitrary; Rather, it was based on specific controls and standards In this research, I tried to approach the abnormal readings according to the linguistic preference theory, with its two criteria: the grammatical preference criterion and the usage preference criterion. And the choice adopted by scholars.